Is violent radicalisation associated with poverty, migration, poor self-reported health and common mental disorders? - Kamaldeep Bhui; Nasir Warfa; Edgar Jones (PLoS ONE, 2014)
Background Doctors, lawyers and criminal justice agencies need methods to assess vulnerability to violent radicalization. In synergy, public health interventions aim to prevent the emergence of risk behaviours as well as prevent and treat new illness events. This paper describes a new method of assessing vulnerability to violent radicalization, and then investigates the role of previously reported causes, including poor self-reported health, anxiety and depression, adverse life events, poverty, and migration and socio-political factors. The aim is to identify foci for preventive intervention. Methods A cross-sectional survey of a representative population sample of men and women aged 18-45, of Muslim heritage and recruited by quota sampling by age, gender, working status, in two English cities. The main outcomes include self-reported health, symptoms of anxiety and depression (common mental disorders), and vulnerability to violent radicalization assessed by sympathies for violent protest and terrorist acts. Results 2.4% of people showed some sympathy for violent protest and terrorist acts. Sympathy was more likely to be articulated by the under 20s, those in full time education rather than employment, those born in the UK, those speaking English at home, and high earners (>£75,000 a year). People with poor self-reported health were less likely to show sympathies for violent protest and terrorism. Anxiety and depressive symptoms, adverse life events and socio-political attitudes showed no associations. Conclusions Sympathies for violent protest and terrorism were uncommon among men and women, aged 18-45, of Muslim heritage living in two English cities. Youth, wealth, and being in education rather than employment were risk factors.